Aspirin associated with a decreased incidence of uterine cancer: A retrospective population-based cohort study. Issue 31 (31st July 2020) - Li, Pei-Chen; Sung, Fung-Chang; Yang, Yu-Cih; Chen, Weishan; Wang, Jen-Hung; Lin, Shinn-Zong; Ding, Dah-Ching
Abstract : Abstract: Aspirin (ASA) exerts an anti-tumor effect via the COX pathway. Clinical studies on the chemopreventive effects of ASA on uterine cancer (UC) remain inconsistent. We used population-based retrospective cohort study to evaluate the UC in ASA users in Taiwanese women. From insurance claims data, we identified 23, 342 women received ASA treatment between 2000 and 2010 and a comparison group of same sample size randomly selected from the same database matched by the propensity score. The incidence of UC in the ASA cohort was 10% of that in the comparison group (0.28 vs 2.73 per 10, 000 person-years). The Poisson regression analysis estimated adjusted incidence rate ratio (IRR) was 0.10 (95% confidence interval (CI) = 0.09–0.11) for ASA users relatives to comparisons after controlling for covariates. The UC incidence in ASA users decreased with age, from 0.61 per 10, 000 person-years in the 20 to 39 years old (adjusted IRR = 0.21, 95% CI = 0.15–0.29) to 0.21 per 10, 000 person-years in the 65 to 80 years old (adjusted IRR = 0.15, 95% CI = 0.12–0.16). The incidence was higher in longer term users. Hormone therapy of estradiol was associated with the increase of UC risk in both cohorts, but less in ASA users than comparisons (1.34 vs 4.75 per 10, 000 person-years). This study suggests that ASA use was associated with a decreased risk of UC. Further prospective randomized clinical trials are warranted to confirm the association.